Peran Tepung Mocaf yang Diperkaya Tepung Cangkang Telur terhadap Kadar kalsium, Densitas, dan Panjang Tulang Tikus Sprague Dawley - Sholikatun Nikmah; Nurhidajah -; Siti Aminah (Universitas Muhammadiyah Semarang, 2017)
The mocaf flour is a fermented flour made from cassava that the mocaf flour contain only slight mineral. The aim of the researt was to find out the effect of consuming the mocaf flour with egg shell powder enrichment towards calcium’s contain, length and density of Sprague Dawley Rat’s Tibia Bone. The studies method was experiment kind using Randomized Complete Block Design (RCBD) which was arranged consist of three treatments of food composition group: Treatment I (AIN 93 standar food), Treatment II ( mocaf flour with 5 % eggshell powder subtitution) and Treatment III (mocaf flour with 10 % eggshell powder substitution). The result of this study showed that the calcium content had different score in each treatment. The lowest score of the bones density was 1,2 g/cm3 in the group treatment III (mocaf flour with 10 % eggshell powder substitution) and the highest score was in the group treatment II (mocaf flour with 5 % eggshell powder substitution). The rat’s bones from all treatment had the same average length. There were no influence of the mocaf flour with egg shell powder enrichment’s consumption in the rat’s tibia bones length and density. Keywords: Mocaf; egg shells; bones